Understanding Transatlantic Cultural Mobility: For a Cross-reading of Fitón in Calderón de la Barca’s «El laurel de Apolo» and Alonso de Ercilla’s «La Araucana» - Mattza, Carmela (Anuario Calderoniano, 2023)
This essay focuses on the intertextual origins and depiction of Fitón in Calderón de la Barca’s play El laurel de Apolo. After contrasting Calderón’s depiction of Fitón with those in Ovid’s Metamorphoses and Alonso de Ercilla’s La Araucana, I demonstrate the special significance Calderón’s variations on the classical myth of Fitón acquires when considered within the context of the intersection of Early Modern Spanish literature, history, arts, and politics. Here, I argue that Calderón’s recasting of Fitón serves as propaganda, the origins of which can be found in the four Titian paintings commissioned by María de Hungría in 1548. These paintings, like Calderón’s Fitón, served as warnings to those who challenged established authority. The essay concludes by examining the transatlantic cultural mobility of Calderón’s conception of Fitón, which enables the playwright to both reinforce the authority of Philip IV and comment on the myth and mythmaking of his Privado, or prime minister, the Count-Duke Olivares. Este ensayo se centra en los orígenes intertextuales y la representación de Fitón en la obra El laurel de Apolo de Calderón de la Barca. Después de contrastar la descripción calderoniana de Fitón con las que aparecen en Las Metamorfosis de Ovidio y La Araucana de Alonso de Ercilla, este estudio muestra el significado especial que adquieren las variaciones de Calderón sobre el mito clásico de Fitón cuando se las considera dentro del horizonte de interpretación formado por la intersección de la literatura, la historia, las artes y la política de la Edad Moderna española. Este ensayo sostiene que la reformulación de Fitón por parte de Calderón sirve como una forma de propaganda, cuyo origen se pueden encontrar en las cuatro pinturas de Tiziano encargadas por María de Hungría en 1548. Estas pinturas, como la recreación de Fitón por Calderón, sirvieron como advertencias para quienes desafiaban la autoridad establecida. El ensayo concluye examinando la movilidad cultural transatlántica de la concepción calderoniana de Fitón, la que le permite al dramaturgo reforzar la autoridad de Felipe IV y comentar tanto el mito surgido como la creación de mitos sobre su Privado, el Conde-Duque Olivares. PALABRAS CLAVE / KEYWORDS: Laurel de Apolo; Fitón; ekphrasis; The Furias; Titian; La Araucana; Count-Duke of Olivares; María de Hungría; Propaganda; Cultural mobility; Cultural object; Transatlantic cultural networks; Palacio del Buen Retiro; Torre de la Parada; Mythography / El Laurel de Apolo; Fitón; écfrasis; La sala de las Furias; Tiziano; La Araucana; Count-Duke of Olivares; María de Hungría; propaganda; redes culturales transatlánticas; movilidad cultural; objeto cultural; Palacio del Buen Retiro; Torre de la Parada; Mitografía.